A new green lacewing species of the extinct subfamily Limaiinae (Insecta: Neuroptera: Chrysopidae) from the mid-Cretaceous of Myanmar. (December 2022) - Chen, Zuluan; Jouault, Corentin; Li, Hongyu; Xu, Chunpeng; Nel, André; Huang, Diying; Liu, Xingyue
Abstract: Chrysopidae (green lacewings) is one of the species-rich families of Neuroptera. The Cretaceous fossils of green lacewing currently comprise 11 genera and 26 species. Here we describe a new green lacewing species, Mesypochrysa coadnata sp. nov., from mid-Cretaceous Burmese amber of northern Myanmar. The new species belongs to the extinct subfamily Limaiinae and is characterized by the RP with seven zigzagged branches, the forewing CuA with four pectinate branches, and the hind wing CuA with three pectinate branches. The exquisite preservation of the new fossils facilitates the understanding of the genital morphology of the Mesozoic green lacewings.